Comparison of 7.2% hypertonic saline - 6% hydroxyethyl starch solution and 6% hydroxyethyl starch solution after the induction of anesthesia in patients undergoing elective neurosurgical procedures (Clinics, 2013)
OBJECTIVE: The ideal solution for fluid management during neurosurgical procedures remains controversial. The aim of this study was to compare the effects of a 7.2% hypertonic saline - 6% hydroxyethyl starch (HS-HES) solution and a 6% hydroxyethyl starch (HES) solution on clinical, hemodynamic and laboratory variables during elective neurosurgical procedures. METHODS: Forty patients scheduled for elective neurosurgical procedures were randomly assigned to the HS-HES group orthe HES group. Afterthe induction of anesthesia, patients in the HS-HES group received 250 mL of HS-HES (500 mL/h), whereas the patients in the HES group received 1,000 mL of HES (1000 mL/h). The monitored variables included clinical, hemodynamic and laboratory parameters. Chictr.org: ChiCTR-TRC-12002357 RESULTS: The patients who received the HS-HES solution had a significant decrease in the intraoperative total fluid input (p